KRITIK HADITS DALAM KAWASAN KAJIAN SEJARAH - Rahmi Rahmi; Taufiqurrahman Taufiqurrahman (Jurnal Ulunnuha, 2019)
The position of hadith criticism is explicitly directed at the criticism of sanad (external criticism; naqd al-khariji) and matan criticism (internal criticism; naqd al-dakhili) basically based on the existence of hadith as the second source which needs to be maintained so that there is an assessmentcritics of the narrators have a purpose to determine the acceptance or rejection of their narrations which are equipped with comprehensive data about the rawi assessed. in this case it is very possible for various approaches, such as the historical approach as a study area, even the approaches of other social sciences as an effort to understand the behavior formed by certain positions in society. in other words, Scientific Kum Doktriner; do not see the doctrinal aspects of sich, but also the scientific aspects.